STRATEGIES TO ADDRESS COVID-19 VACCINE HESITANCY AMONG OHIO NURSING HOME STAFF. (20th December 2022) - Kunkel, Miranda; Applebaum, Robert; Nelson, Matt
Abstract: Background: Nursing home staff members unvaccinated against COVID-19 pose an ongoing public health risk considering their frequent contact with older adults, a population especially vulnerable to the virus. In order to address vaccine hesitancy and foster vaccine confidence effectively among nursing home staff, evidence-based health communication strategies are necessary. Methods: Using a dataset composed from three sources of Ohio nursing home data, the research questions guiding this study are as follows: 1) What is the relationship between engaging in various strategies to address vaccine hesitancy and vaccination rates among staff?; 2) Does hiring infection preventionists affect vaccination rates among staff? Multivariable linear regression techniques were used to assess all variables. Results: Peer counseling and providing time off to the staff for vaccination statistically significant strategies to reduce vaccine hesitancy among staff. Compared to facilities that did not engage in peer counseling, those that did saw an average increase of 3.6% of their staff vaccinated. Compared to facilities that did not provide time off to their staff for vaccination, those that did saw an average increase of 4.2% of their staff vaccinated. Discussion: Peer counseling should be pursued as a viable strategy for fostering vaccine confidence among nursing home staff and further studied in more diverse populations. Implications for nursing home staff acceptance of facility-wide initiatives will be discussed.